2023
DOI: 10.5334/gh.1211
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Predictors, and Outcomes of Resistant Hypertension in Egyptian Population

Abstract: Background: Hypertension is a leading problem; it affects around thirty million adult Egyptians, according to the last national registry. The exact prevalence of resistant hypertension (RH) in Egypt wasn't spotted before. The purpose of this study was to determine the prevalence, predictors, and impact on adverse cardiovascular outcomes among adult Egyptians with RH. Methods:The present study examined a cohort of 990 hypertensive patients who were divided into two groups based on their blood pressure control; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Moreover, another meta-analysis published in 2023 suggested that more intensive blood pressure-lowering therapy might be associated with a reduced risk of recurrent stroke and major cardiovascular events (Hsu et al, 2023). Therefore, the intervention has the potential to prevent a large number of stroke events and save lives in Egypt, where hypertension is highly prevalent and poorly controlled and it affects around thirty million adult Egyptians, according to the last national registry (Khalfallah, et al, 2023). Another notable finding of the study is the significant improvement in the glycemic control of the study group, as indicated by the remarkable reduction in the percentage of individuals with high haemoglobin A1c (≥6.5%) from 68.6% at pre-intervention to 14.7% at post-intervention as a follow-up, compared to a minimal reduction in the control group from 66.7% to 62.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another meta-analysis published in 2023 suggested that more intensive blood pressure-lowering therapy might be associated with a reduced risk of recurrent stroke and major cardiovascular events (Hsu et al, 2023). Therefore, the intervention has the potential to prevent a large number of stroke events and save lives in Egypt, where hypertension is highly prevalent and poorly controlled and it affects around thirty million adult Egyptians, according to the last national registry (Khalfallah, et al, 2023). Another notable finding of the study is the significant improvement in the glycemic control of the study group, as indicated by the remarkable reduction in the percentage of individuals with high haemoglobin A1c (≥6.5%) from 68.6% at pre-intervention to 14.7% at post-intervention as a follow-up, compared to a minimal reduction in the control group from 66.7% to 62.7%.…”
Section: Discussionmentioning
confidence: 99%